Managing change at Queens : people and technology issues - Thomas, Nobin; Bhatnagar, Deepti (London : SAGE Publications: SAGE Business Cases Originals, 2020)
Today, organizations are undergoing various changes in order to stay abreast with international standards of quality. However, it would be interesting to understand how an education institution, where students are groomed to adapt to change, reacts to the change process being proposed for its advancement. With this background, we attempt to decode the events associated with the technological innovations being brought in the academic space of a higher education institute situated in South India—Queens. The case revolves around Manoj George, Jose Alex, and various other stakeholders who support or oppose the changes affecting Queens. After a successful stint as a young faculty member in a state-run college, George decides to try his luck at Queens, but he is disgruntled with the systemic inefficiencies and lack of technological innovation. Though he is able to convince the director, Alex, of the value of much-needed changes, he is considered an aggravation by the top bosses in the hierarchical ladder, who are conspiring to undermine his entire plan. The unstable leadership, resistance from internal faculty, presence of a power caucus, political maneuvering, dynamic goal-setting, technological redundancy, and obstructive team dynamics create blocks to his endeavor. The case describes George's journey through difficult times at Queens and provides for multiple interpretations. The internal and external forces causing the change, the resistance to the change process, and the power and politics that revolves around change are a few inevitable elements that cannot be ignored at Queens. Students are asked if Alex should continue supporting George and his team in light of the recent events.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Organizational change -- India -- Case studies; Education, Higher -- Technological innovations -- India -- Case studies; Educational innovations -- India -- Case studies